Pauline ugliness : Jacob Taubes and the turn to Paul - Løland, Ole Jakob (Perspectives in continental philosophy., 2020)
Jacob Taubes radically changed our conceptions of Paul the apostle. Loland shows how we can approach Paul's letters with the distinctive perspective of this Jewish rabbi steeped in continental philosophy. The book emphasizes Paul's Jewishness as well as the political explosiveness of the apostle's revolutionary doctrine of the cross, which the author terms Pauline Ugliness.